Leveraging fuel subsidy reform for transition in Yemen - Breisinger, Clemens; Engelke, Wilfried; Ecker, Olivier (MDPI, 2012)
Yemen is currently undergoing a major political transition, yet many economic challenges—including fuel subsidy reform—remain highly relevant. To inform the transition process with respect to a potential subsidy reform, we use a dynamic computable general equilibrium and microsimulation model for Yemen; we show that overall growth effects of subsidy reduction are positive in general, but poverty can increase or decrease depending on reform design. A promising strategy for a successful reform combines fuel subsidy reduction with direct income transfers to the poorest one-third of households during reform, and productivity-enhancing investment in infrastructure, plus fiscal consolidation. Public investments should be used for integrating economic spaces and restructuring of agricultural, industrial and service value chains in order to create a framework that encourages private-sector-led and job-creating growth.